The Principle of Trust in Online Buying and Selling Transactions in the Perspective of the Civil Code and Law No.19 of 2016 concerning Information and Electronic Transactions - Yunika Giawa; Irma Fatmawati (Fakultas Hukum Dehasen, 2024)
The principle of trust in online buying and selling transactions is an important foundation in the relationship between sellers and buyers, both from the perspective of the Civil Code and Law No. 19 of 2016 concerning Information and Electronic Transactions. This research is a qualitative normative research on law. This study aims to analyze the role of the principle of trust in creating safe and efficient transactions online. By emphasizing the good faith and obligations of the parties, the study found that trust not only guarantees the fulfillment of rights and obligations, but also increases the effectiveness of transactions. In addition, this study also found that despite having rules, Indonesia is still not fully optimal in regulating online transactions. Basically, clear regulations in the e-law provide a strong legal foundation to support the buying and selling process, thus creating a conducive environment for the growth of e-commerce in Indonesia